Rate –limiting steps of the oxygen reduction reaction in REBa2Cu3O6+ẟ (RE = La, Nd, Sm, Gd and Y) layered perovskites as IT-SOFC cathodes - Grassi, J. (2025)
The classical high-temperature superconductor YBa2Cu3O6+δ (YBCO) with an oxygen-vacant triple perovskite structure has been proposed as a potential cathode for Intermediate Temperature Solid Oxide Fuel Cells (IT-SOFCs), and REBa2Cu3O6+ẟ (RE = La, Nd, Sm, Gd and Y) triple perovskites synthesized by a self-combustion method were evaluated. The total substitution of Y by lanthanide ions (RE3+) proved to modify relevant bulk and surface properties, thus changing performance under operating conditions, i.e., the incorporation–diffusion mechanism by oxygen vacancies and oxide anion transport. Electrochemical Impedance Spectroscopy (EIS) under different oxygen partial pressure (pO2) and temperature (T) conditions allowed elucidating a co-limited oxygen incorporation/diffusion mechanism as Oxygen-Reduction Reaction (ORR) limiting steps. Ionic radii (ri) variation from Y3+ to La3+ impacts the kinetics of the two steps, thereby modifying the overall cathode performance. The results provide evidence of the complex relationship between crystallography, point defect concentration, chemical composition and electrochemical properties in REBCO cathodes. Data suggest that the Cu-O bond distance in cuprates may be critical for shifting the rate-limiting step and improving ORR activity. Overall, this research advances the comprehension of ORR kinetics in cobalt-free materials with layered diffusion.